Prediction of Pressure Profile During Multi-Phase Flow in Different Oil Well: A Comparative Study - Satar, Raya; Baker, Hussain Ali (Iraqi Journal of Science, 2020)
Multiphase flow is a very common phenomenon in oil wells. Several correlation models, either analytical or experimental, have been investigated by various studies to investigate this phenomenon. However, no single correlation model was found to produce good results in all flow conditions. 14 models available on the Prosper software were selected for the purpose of calculating the pressure gradient inside wells within a range of different flow conditions. The pressure gradient was calculated using Prosper software, then compared with the measured gradient based on the production log test (PLT) data. This study was conducted on 31 wells from five different oil fields (Kirkuk, Jambur, Bai-Hassan, Al-Ahdab, and Rumaila). It is worth noting that these wells have not been studied previously. The results indicated that the best correlation models were the Original Duns and Rose (DRO), Petroleum Experts 2 (PE2), and Hagedorn and Brown (HB), which outperformed the models of Hydro-3p and Mukherjee and Brill. The calculations also showed that the overall performance of all correlations is generally better in two-phase flow wells. Despite this, Fancher and Brown (FB), Hydro-3p, HB, and Orkiszewski (OR) models demonstrated an improved performance in three-phase flow wells as compared to the other correlation models.